Potassium management for corn growth, yield and sweetness under Sabah sandy soil - Athirah Amran; Mohamadu Boyie Jalloh; Mohd. Dandan @ Ame Alidin; Elisa Azura Azman; Roslan Ismail; Shiva Dhar; Sanjeev Kumar Rana; Kamal Garg; Sunny Goh Eng Giap (Karya ilham publishing, 2024)
A study was conducted to determine the effect of potassium (K) with organic fertilizers on the growth, yield and sweetness of reddish waxy corn. The treatments were: (T1) standard fertilizer rate of 60 kg ha-1 K2O without organic fertilizer (control); (T2) 30 kg ha-1 K with organic fertilizer; (T3) 90 kg ha-1 K with organic fertilizer and (T4) 120 kg ha1 K with organic fertilizer. Organic fertilizer used was 1.5 t ha-1 Bokashi and 20 t ha-1 chicken manure biochar (CMB). The planted corn received 120 kg ha-1 N and 60 kg ha1 P2O5. The experimental design was Completely Randomized Design (CRD) with six replications. Stem girth, number of leaves, the height of the first cob, fresh weight of the first cob, 100 grains weight, cob girth, cob length and sweetness (Brix scale, %) data were analyzed using ANOVA (Analysis of Variance) at 5% significant levels. The Least Significant Different (LSD) was used to compare the means for significantly different results. Significant differences in growth were obtained at (p<0.05) in waxy corn for the number of leaves, the height of the first cob, length of cob, and girth between the control and all treatments. However, there is no significant difference for the sweetness of waxy corn for all treatments. Mean total for growth parameters; the number of leaves, stem girth and height of the first cob from soil surfaces and mean total for yield parameters; cob girth, length of cob, fresh weight of cob, 100 grains weight and the number of kernels was significantly higher for all treatments of T2, T3 and T4 compared to control the treatment of T1. The study showed no significant difference in the sweetness of waxy corn with increasing potassium application, resulting in increased total soluble content. Similar studies for a different rate of organic fertilizers and soil analysis can be done to ascertain further the effects on growth, yield, and sweetness parameters of reddish waxy corn with selected soil properties.